PENGARUH PEMILIHAN TATA LETAK PRODUK, HARGA DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA ROYAL ATK (Studi Kasus Mahasiswa FEB Angkatan 2016 Universitas Islam Malang) - Yati Ambarwati; N. Rachma; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This research tests and analyzes the influence of product layout, price and product completeness to purchasing decisions on Royal ATK Mall Dinoyo City. The population in this study was a FEB student of 2016 Islamic University of Malang which is not known for certain numbers so samples used Malhotra 110 people. The method used is multiple linear regression analysis, using the t test and F test for the hypothesis. The results of this study prove that simultaneously the product layout, price and product completeness have a significant effect on decisions purchasing. While partially each price and product completeness variables have a significant effect on purchasing decisions, but the product layout variable no hassignificant effect on purchasing decisions. Keywords: Product Layout, Price, Product Completeness, Purchase Decision.